2018
DOI: 10.20944/preprints201808.0250.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Full-Scale Comparative Study of Conventional and Side-Stream Enhanced Biological Phosphorus Removal Processes

Abstract: In this study, a full-scale pilot testing was performed with side-by-side operation of a conventional enhanced biological phosphorus removal (EBPR) process and a side-stream EBPR (S2EBPR) process. A comparison of the performance, activities and population dynamics of key functionally relevant populations between the two configurations were carried out. The results demonstrated that, with the same influent wastewater characteristics, S2EBPR configuration showed more effective and stable orthophosphate (PO4-P) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…On the other hand, a low carbon environment was always maintained, which was considered to encourage the growth of PAO than GAO as the latter could not survive well in low carbon environment (Tu, 2012). A recent study also reported that PAO could be favored against GAO by the side-stream sludge hydrolysis or a longer anaerobic period (Wang et al, 2018), which agreed the previous work of Stokholm-Bjerregaard et al (2015). Further study would be required to investigate on the competition between PAO and GAO with continuous low carbon supply under warm climate.…”
Section: Sndpr Performance In Full-scale Wrpsupporting
confidence: 89%
“…On the other hand, a low carbon environment was always maintained, which was considered to encourage the growth of PAO than GAO as the latter could not survive well in low carbon environment (Tu, 2012). A recent study also reported that PAO could be favored against GAO by the side-stream sludge hydrolysis or a longer anaerobic period (Wang et al, 2018), which agreed the previous work of Stokholm-Bjerregaard et al (2015). Further study would be required to investigate on the competition between PAO and GAO with continuous low carbon supply under warm climate.…”
Section: Sndpr Performance In Full-scale Wrpsupporting
confidence: 89%
“…2). Second, our previous study via Ramanbased observation suggested that the PHA-containing cells were significantly higher in the S2EBPR system in comparison to those in the conventional EBPR systems (Wang et al, 2021;Wang et al, 2018). Coupling of internal carbon (PHA) utilization and partial denitrification were also observed by others (Ji et al, 2017;Krasnits et al, 2013;Tu et al, 2019;Wang et al, 2019b).…”
Section: Partial Denitrification Associated With Internal Carbon Util...mentioning
confidence: 85%
“…Before performing the activity test, a 30‐min aeration was applied to deplete the sludge from remaining organics to obtain a soluble COD <20 mg/L (Wang et al, 2018). This pre‐aeration step ensures the designed initial COD concentration is achieved in the batches.…”
Section: Methodsmentioning
confidence: 99%